Penerapan inventory tes gaya belajar remaja dengan aplikasi google form, media sosial serta pengembangan program layanan bimbingan dan konseling terkait - Yuyun Mashurwati (Indonesian Institute for Counseling, Education and Therapy (IICET), 2018)
Student learning outcomes are low and not optimal is a common problem that occurs in adolescents in almost all schools in Indonesia. One reason, teachers are less than optimal in accommodating student learning styles. This text tries to offer an alternative that teachers can do, especially BK teachers / counselors, to introduce learning styles using very easy-to-create applications using the google form application and utilizing social media for socialization. This paper only provides a brief description, so for the future need further research and follow-up.